Insights from DOCK2 in cell function and pathophysiology - Ji, Lulin; Xu, Shuquan; Luo, Haiqing; Zeng, Fanwei (Frontiers in Molecular Biosciences, 2022)
Dedicator of cytokinesis 2(Dock2) can activate the downstream small G protein Rac and regulate cytoskeletal reorganization. Dock2 is essential for critical physiological processes such as migration, activation, proliferation, and effects of immune cells, including lymphocytes, neutrophils, macrophages, and dendritic cells. For example, Dock2 is involved in the development and activation of T and B lymphocytes by affecting synapse formation and inhibiting the development of the Th2 lineage by downregulating IL-4Rα surface expression. Not only that, Dock2 may be a molecular target for controlling cardiac transplant rejection and Alzheimer's disease (AD). Patients with defects in the DOCK2 gene also exhibit a variety of impaired cellular functions, such as chemotactic responses of lymphocytes and reactive oxygen species (ROS) production by neutrophils. To date, Dock2 has been shown to be involved in the development of various diseases, including AD, pneumonia, myocarditis, colitis, tumors, etc. Dock2 plays different roles in these diseases and the degree of inflammatory response has a different impact on the progression of disease. In this paper, we present a review of recent advances in the function of Dock2 in various immune cells and its role in various diseases.